Novel air‐filled substrate integrated waveguide bandpass filter with nonresonant node structures. Issue 12 (23rd July 2021) - Wu, Yongbiao; Yang, Kai; Chen, Peng; Zhang, Lanhai; Li, Guopeng
Abstract: A low‐loss bandpass filter with a nonresonant node (NRN) based air‐filled substrate integrated waveguide (SIW) is proposed in this study. It is based on a second‐order inductive diaphragm‐coupled filter with an additional NRN to introduce a transmission zero (TZ) in the upper stopband. Measured results show that the filter has a center frequency of 32.27 GHz with the bandwidth of 0.9 GHz. The insertion loss in the passband is 1.2 dB, and the return loss is better than 24 dB. Due to the presence of TZ in the upper sideband, the AFSIW filter has a sharper transition performance and achieves good selectivity.